Comparative literature in contemporary Romania - Terian, Andrei (Primerjalna književnost, 2013)
This paper examines the current state and prospects of comparative literature in Romania. Romanian literary studies in the 20th century was characterized by the subordination of comparative perspectives to the national literary historiography, the absence of a strong local methodological tradition, and the dominance of an essayistic and impressionistic brand of criticism. The study focuses on forms of institutionalization of comparative studies in postcommunist Romania (associations, research centers, journals, etc.) and the emergence of several comparative schools (particularly those in Timişoara, Cluj and Braşov).
Keywords: primerjalna književnost; comparative literature; Romania; Romunija; romunska literarna veda; postkomunizem; institucionalizacija; internacionalizacija